PERLUASAN HARNACK DAN SIFAT CAUCHY INTEGRAL HENSTOCK-DUNFORD PADA RUANG EUCLIDE - ., Solikhin (MATEMATIKA, 2013)
In this paper we study Henstock-Dunford integral on the Euclidean space . We discuss some properties of the integrable. We proveÂ the Harnack Extension theorems and the Cauchy extension theorems for Henstock-Dunford integral on the Euclidean space .